Study on the Design Method for the Deformation State Control of Pile-Anchor Structures in Deep Foundation Pits - Jinkun Sun; Senping Wang; Xinjun Shi; Feng Wu; Liyun Zeng (Advances in Civil Engineering)
At present, the design of pile-anchor structures for deep foundation pits can be divided into the limit state control design of the bearing capacity and the limit state control design in normal use (i.e., “deformation state control design”). Strength design focuses on the strength control of supporting structures and rock-soil masses, while deformation design focuses on the deformation and environmental impact control of supporting structures and rock-soil masses. However, since a rock-soil mass, especially a soil mass, is a rheid, the strength control design process is not completely reliable, and the deformation control design is also required when the rheological behavior is prominent. A pile-anchor structure can limit the deformation of supporting structures by applying a prestress, with good technical and economic benefits; therefore, it has been widely used in the support engineering of deep foundation pits. In this paper, the objective of the deformation state control of pile-anchor structures for deep foundation pits, the corresponding stress level thresholds, and the determination of the bearing capacity checkpoint are studied based on the strength parameters of the soil deformation state and by combining a theoretical calculation analysis of the stress mode of pile-anchor structures, the calculations of previous engineering cases, and finite element simulation. Based on the depth of the plastic zone of the soil in the built-in section of the foundation pit supporting the structure, the position of the deformation state checkpoint of the soil in the built-in section inside the foundation pit is determined as one-third of the length hd of the built-in section below the bottom of the foundation pit; the stress level threshold λ(2) corresponding to the slow, steady state is determined as approximately 30%–60% based on the curve characteristics of the relationship between the deformation and the stress level of the soil in the built-in section (1/3)hd below the bottom of the foundation pit. Based on the stress mode and deformation control requirements of the anchorage section of the pile-anchor structure and the Mohr–Coulomb strength criterion, the deformation state control design method of the pile-anchor structure is constructed by taking the deformation state bearing capacity at (1/3)hd as the checkpoint and the stress level threshold λ(2) corresponding to the slow, steady state.